Practical blood flow restriction training increases muscle hypertrophy during a periodized resistance training programme. (4th November 2013) - Lowery, Ryan P.; Joy, Jordan M.; Loenneke, Jeremy P.; de Souza, Eduardo O.; Machado, Marco; Dudeck, Joshua E.; Wilson, Jacob M.
Summary Background Resistance training in combination with practical blood flow restriction (pBFR) is thought to stimulate muscle hypertrophy by increasing muscle activation and muscle swelling. Most previous studies used the KAATSU device; however, little long‐term research has been completed using pBFR. Objective To investigate the effects of pBFR on muscle hypertrophy. Methods Twenty college‐aged male participants with a minimum of 1 year of resistance training experience were recruited for this study. Our study consisted of a randomized, crossover protocol consisting of individuals either using pBFR for the elbow flexors during the first 4 weeks (BFR‐HI) or the second 4 weeks (HI‐BFR) of an 8‐week resistance training programme. Direct ultrasound‐determined bicep muscle thickness was assessed collectively at baseline and at the end of weeks 4 and 8. Results There were no differences in muscle thickness between groups at baseline (P = 0·52). There were time (P<0·01, ES = 0·99) but no condition by time effects (P = 0·58, ES = 0·80) for muscle thickness in which the combined values of both groups increased on average from week 0 (3·66 ± 0·06) to week 4 (3·95 ± 0·05) to week 8 (4·11 ± 0·07). However, both the BFR‐HI and HI‐BFR increased significantly from baseline to week 4 (6·9% and 8·6%, P<0·01) and from weeks 4 to 8 (4·1%, 4·0%, P<0·01), respectively. Conclusion The results of this study suggest that pBFR can stimulate muscle hypertrophy to the same degree to that of high‐intensity resistance training.